PENGARUH BRAND IMAGE DAN KUALITAS LAYANAN TERHADAP KEPERCAYAAN DAN KEPUTUSAN PEMBELIAN PADA TOKO ONLINE (Studi pada Konsumen OLX.co.id di Kota Semarang) - Febriani, Roro Ratih; Sudaryanto, Budi (Diponegoro Journal of Management, 2018)
The development of technology makes life more modern, people want everything can be accomplished quickly andÂ  easily,Â  so it makes many e-commerce spring up in Indonesia. This study aims to analyze the brand image and service quality on the trust and its impact on purchasing decisions in OLX.co.id site.The population of the study was all consumers who had ever done purchase transaction on OLX.co.id site, where the respondents are the people who domicile in Semarang city. The samples in this study were 150 respondents. The method of collecting data through questionnaires. This study uses analytical techniques of Structural Equation Modeling (SEM) with AMOS 22.0 as the analysis instrument.The result of this study show that the brand image has a positive and significant effect on trust, brand image has a positive and significant effect on purchase decision, service quality has a positive and significant effect on trust, service quality has a positive and significant effect on purchase decision, and trust has a positive and significant effect on purchase decision.